Eksplorasi Pemanfaatan dan Konservasi Spesies Tumbuhan di Kawasan Taman Gumi Banten Berbasis Kearifan Lokal di Desa Wanagiri Kecamatan Sukasada Kabupaten Buleleng - Luh Putu Amelia Rahayu; Nyoman Wijana; Sanusi Mulyadiharja (Jurnal Pendidikan Biologi Undiksha, 2022)
This study aims to determine: (1) Utilization of plant species by the community in Wanagiri Village, (2) Composition of useful plant species, and (3) Conservation of plant species based on local wisdom of the community in Wanagiri Village. The type and design of this research is descriptive exploratory. This research was conducted in the Taman Gumi Banten Forest, Wanagiri Village. The samples in this study include ecosystem parameters and sociocytem parameters, samples on ecosystem parameters, namely useful plants found in 86 squares with a size of 1 x 1 meter for seedlings, 10 x 10 meters for saplings and poles, 20 x 20 meters for trees, and sociocytem parameters, namely 20 people from 2 official village officials, 3 community leaders, 5 general public, 3 senior officials, and 7 STT people. The results of this study are: (1) All ceremonial plants are used as ceremonial infrastructure, (2) The composition of useful plant species belongs to 34 families which are dominated by bananas (Musa paradisiaca), (3) Plant conservation efforts can be carried out by applying wisdom local, religious aspects, myths, and local village awig-awig.